The Activity of Metalloproteases and Serine Proteases in Various Organs after Leiurus macroctenus Envenomation - Valery Gunas; Oleksandr Maievskyi; Nataliia Raksha; Tetiana Vovk; Oleksiy Savchuk; Serhii Shchypanskyi; Igor Gunas (Journal of Toxicology)
Background. Scorpion stings may be life-threatening since their venoms are comprised of a wide range of toxins and other bioactive molecules, such as enzymes. At the same time, scorpion envenomation may increase matrix metalloproteases (MMPs) levels, which enhance proteolytic tissue destruction by venom. However, investigations on the impact of many scorpions’ venoms, such as those of Leiurus macroctenus, on tissue proteolytic activity and MMP levels have not yet been conducted. Methods and Results. The present study aimed to examine the total proteolysis levels in various organs after Leiurus macroctenus envenomation and evaluate the metalloproteases and serine proteases’ contributions to the total proteolytic activity. Changes in MMPs and TIMP-1 levels were tested as well. Envenomation led to a significant increase in proteolytic activity levels in all assessed organs, mostly in the heart (by 3.34 times) and lungs (by 2.25 times). Conclusions. Since EDTA presence showed a noticeable decrease in total proteolytic activity level, metalloproteases appeared to play a prominent role in total proteolytic activity. At the same time, MMPs and TIMP-1 levels were increased in all assessed organs, suggesting that Leiurus macroctenus envenomation causes systemic envenomation, which may induce multiple organ abnormalities, mostly because of the uncontrolled metalloprotease activity.